Exploration of Attractive Learning Media: DeBuTon Sounding Book - Telaumbanua, Angeline Berlian Christiana; Daneswari, Kun Faradhillah; Pramesti, Revalina Agdya; Aini, Desti Nur (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2024)
This article discusses the development of a learning media titled "DeBuTon Sounding Book" designed to support the learning of Ger- man at A1 level. Learning media has a crucial role in creating an attractive and fun learning environment. The development of "DeBuTon Sounding Book" is in accordance with technological ad- vances and serves as a tool in achieving educational goals. The purpose of this research involves a description of the use of "DeBuTon Sounding Book" as well as an understanding of student responses to the media. The research method used the ADDIE model which involves the stages of analysis, design, development, implementation, and evaluation. Through the analysis and evalu- ation stages, this article provides an overview of the development of "DeBuTon Sounding Book" learning media to support the learn- ing of German language at A1 level. Overall, this article aims to contribute to improving the quality of German language learning at the high school level as well as proposing ideas for developing more attractive learning media according to students’ needs. Keywords: Learning media, attractive, German.